Memasyarakatkan Tanya 5O Dan Efek Interaksi Obat Pada Siswa MTsN 2 Kota Palangka Raya: Promoting “Tanya 5 O” and Effects of Drugs on Nutritional Status in Students of MTsN 2 Palangka Raya - Harlyanti Muthma'innah Mashar; Normila Normila; Juni Ramadhani; Dali Dali; Ismail Ismail (Jurnal Mandala Pengabdian Masyarakat, 2021)
This community service is a form of sharing program of cooperation from the Ministry of Health of the Republic of Indonesia and the Provincial and City Health Offices, namely GeMa CerMat (Smart Community Movement Using Drugs), one of which is through the promotion of the tagline "Tanya Lima O". Through this tagline, it is hoped that the public can be more active in seeking information about drugs, not only for health workers but also from other valid and trustworthy sources. Apart from this information, people also need to know drug interactions, especially drug interactions with food. To achieve quality and safe drug use, active community involvement is highly expected. In this activity, the target audience is students at MTsN 2 Palangka Raya. The method is in the form of the posttest and pretest implementation, interactive counseling with participants, as well as discussion and question and answer. The value obtained from the posttest and pretest results was then performed statistical tests using the paired T-test and the Gain test. Based on the results of the analysis, it was found that there was a significant difference in knowledge between before and after counseling was given. This is evidenced by the increase in post-test scores. The average posttest score was 80, and this value was greater than the pretest average score of 44. The results of the analysis with the paired T-test obtained p-value = 0.000, indicating a significant difference in knowledge between before and after counseling. The value of understanding that increased after being given counseling was shown by a percentage of 87.69%, consisting of 25 people (38.46%) who obtained high gain values ??and 32 people (49.23%) moderate gain values.